Forført til landsforræderi. Hvervning og skoling af danske frivillige i Waffen SS, sommeren 1940 - Hansen, Peter Møller (Historisk Tidsskrift, 2013)
Seduced to Treason Recruitment and Schooling of Danish SS Volunteers in the Summer of 1940In the spring of 1940, the imperial project of the German NS-regime motivated SS Reichsführer Heinrich Himmler to initiate a determined recruitment program amongst the youth of the occupied Northern-European countries. In Denmark this attempt to mobilize young men for the German war effort was concealed to the public as it went against an agreement between the Danish government and the German occupants. Even the Wehrmacht – the regular German army, which opposed the rapid expansion of the SS – was kept in the dark on this matter. German as well as Danish staffs were actively involved in the recruitment drive. As soon as Frits Clausen, leader of the Danish National Socialist Party (DNSAP) had authorized party leaders to assist the project, secret sessions, complete with medical boards etc., began to take place in Danish cities. The target was set at 300 recruits who soon after would go to initial training in Klagenfurt, Austria, at the newly established SS Regiment Nordland. Volunteers appeared from both inside and outside National Socialist circles, but neither military nor party officials imparted to them any precise knowledge of the scheme. On the contrary, recruiters led applicants to believe that they were going to Klagenfurt to attend a prolonged political course in order to prepare themselves for attractive positions in a society ruled by the National Socialists after the war. On their arrival in Austria, the volunteers were surprised to learn that theywere expected, here and now, to enlist in the Waffen SS, signing a contract of no less than two years of war service. The future battlefield, of course, remained undisclosed to the volunteers. Some of the groups were told they would go to war against England, thus clearing the ground for a unified Europe under German command. According to the German commanders in Nordland, this would be tantamount to Denmark losing her sovereignty. A number of volunteers nevertheless agreed to sign a contract while the rest refused, partly because of the nationalistic issue regarding Denmark’s role in a future united Europe, but also due to the fact that they felt they had been duped. Those who agreed to enlist were immediately put to work in a demanding military training program, while those who refused were separated from the others. The local commanders, unprepared to face such massive reluctance, finally presented them with the choice of either going home immediately, or, instead, participate in a program of political education combined with some military exercise. Under these conditions, a minor part opted for staying while the majority went directly back to Denmark. The ensuing process of indoctrination aimed to convince the volunteers of the benefits from a unified Europe under German command. Apart from that, an overall introduction to National Socialist ideology, with a specific focus on how it applied within a Danish context, weighed heavily in the curriculum. The effect on the minds of the participants is difficult to judge from the available sources. Some participants were receptive as they already adhered to the NS movement; on the other hand, it appears doubtful that many of them were able to engage properly in the program, given the fact that the teaching was in German. At any rate, only few of them later revised their decision not to join the SS military corps. Out of 300 Danish recruits, 185 signed a service contract and were still in Regiment Nordland at the end of 1940. This is a much higher figure than indicated by previous estimates, but not many of them were drawn from those who took the politico-ideological course.